2009
DOI: 10.1377/hlthaff.28.5.w978
|View full text |Cite
|
Sign up to set email alerts
|

Using Clinical Information To Project Federal Health Care Spending

Abstract: ABSTRACT:Complications from chronic illnesses often do not emerge for many years. Current federal cost projection methods are constrained by ten-year cost estimates, which capture increases in near-term intervention costs but not changes in long-term costs. Current methods also cannot easily capture the cost implications of changes in disease progression. Type 2 diabetes is a prime example of a chronic illness with long-term health and cost consequences. We present results from an epidemiologically based model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…A ten-year time horizon is generally used by the Congressional Budget Office, but this time frame has been criticized as inadequate to show the full effects of interventions that prevent disease onset or alter the trajectories of chronic diseases. 10 Thus, we show longer-term results as well.Previous analyses using this model have shown that expanding primary care capacity can greatly enhance the ability of coverage and care interventions to improve health and costeffectiveness. 1 We therefore conducted sensitivity tests to examine how the sufficiency of primary care capacity might affect each simulated scenario.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…A ten-year time horizon is generally used by the Congressional Budget Office, but this time frame has been criticized as inadequate to show the full effects of interventions that prevent disease onset or alter the trajectories of chronic diseases. 10 Thus, we show longer-term results as well.Previous analyses using this model have shown that expanding primary care capacity can greatly enhance the ability of coverage and care interventions to improve health and costeffectiveness. 1 We therefore conducted sensitivity tests to examine how the sufficiency of primary care capacity might affect each simulated scenario.…”
supporting
confidence: 67%
“…A ten-year time horizon is generally used by the Congressional Budget Office, but this time frame has been criticized as inadequate to show the full effects of interventions that prevent disease onset or alter the trajectories of chronic diseases. 10 Thus, we show longer-term results as well.…”
supporting
confidence: 67%
“…This GCC study argues that in the absence of population adjustment measures, it could result in an oversupply of health-care resources, which might lead to changes in behaviours such as supplier-induced demand or an underproductive health workforce. Huang et al constructed a spending projection model for diabetes, in order to inform health-care budget decisions in the United States (23). Within the United States, health-care costs are rising, due to significant pressure from demographic forces such as a growing elderly population (23).…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al constructed a spending projection model for diabetes, in order to inform health-care budget decisions in the United States (23). Within the United States, health-care costs are rising, due to significant pressure from demographic forces such as a growing elderly population (23). The population size of people with diabetes was used as a base for projections, with the expectation that more individuals would become diabetic as they aged.…”
Section: Discussionmentioning
confidence: 99%
“…This rise is theorized to be due to rising clinical incidence of the condition because diagnosed diabetes prevalence has increased between 1988-1994 and 1999-2002, but the proportion of diagnosed diabetes cases (out of all diagnosed and undiagnosed diabetes cases) has remained constant over the same period (62). Huang (32) projects that the true clinical incidence of diabetes will stagnate by 2020 as the number of people with undiagnosed and newly diagnosed diabetes decreases, although the treated prevalence of diabetes will continue to increase owing to the combination of higher obesity rates and better disease detection.…”
Section: Evidence Of Treated Prevalence and Spending Per Case Treatedmentioning
confidence: 99%